An Empirical Assessment of Reviewer 2. (April 2022) - Worsham, Christopher; Woo, Jaemin; Zimerman, André; Bray, Charles F.; Jena, Anupam B.
According to research lore, the second peer reviewer (Reviewer 2) is believed to rate research manuscripts more harshly than the other reviewers. The purpose of this study was to empirically investigate this common belief. We measured word count, positive phrases, negative phrases, question marks, and use of the word "please" in 2546 open peer reviews of 796 manuscripts published in the British Medical Journal. There was no difference in the content of peer reviews between Reviewer 2 and other reviewers for word count (630 vs 606, respectively, P = .16), negative phrases (8.7 vs 8.4, P = .29), positive phrases (4.2 vs 4.1, P = .10), question marks (4.8 vs 4.6, P = .26), and uses of "please" (1.0 vs 1.0, P = .86). In this study, Reviewer 2 provided reviews of equal sentiment to other reviewers, suggesting that popular beliefs surrounding Reviewer 2 may be unfounded.